2018
DOI: 10.1101/334656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic, biochemical, and molecular characterization ofMethanosarcina barkerimutants lacking three distinct classes of hydrogenase

Abstract: 17The methanogenic archaeon Methanosarcina barkeri encodes three distinct 18 types of hydrogenase, whose functions vary depending on the growth substrate. 19These include the F420-dependent (Frh), methanophenazine-dependent (Vht), and 20 ferredoxin-dependent (Ech) hydrogenases. To investigate their physiological roles, 21we characterized a series of mutants lacking each hydrogenase in various 22 40 IMPORTANCE 41Methanogenic archaea are key players in the global carbon cycle due to their 42 ability to facilitat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The electrons released from the oxidation of CO moiety end up in the reduction of methyl moiety thus completing the aceticlastic methanogenesis. This H 2 ‐dependent pathway depends very much on the efficiency of Vho to recapture H 2 that may escape the oxidation due to the easy diffusion away from the cell (Welte and Deppenmeier, ; Kulkarni et al ., ; Mand et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The electrons released from the oxidation of CO moiety end up in the reduction of methyl moiety thus completing the aceticlastic methanogenesis. This H 2 ‐dependent pathway depends very much on the efficiency of Vho to recapture H 2 that may escape the oxidation due to the easy diffusion away from the cell (Welte and Deppenmeier, ; Kulkarni et al ., ; Mand et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Like Frh, Vht is a three-subunit enzyme encoded by a four-gene operon ( vhtGACD ) that includes a maturation protease, VhtD ( 19 ). M. barkeri also contains genes that encode homologs of both the frh and vht operons (the freAEGB and vhxGAC operons, respectively); however, multiple lines of evidence suggest that these genes are incapable of producing active hydrogenases ( 16 , 22 ). Thus, the presence of these genes has no bearing on the results presented herein.…”
Section: Resultsmentioning
confidence: 99%
“…Mph is responsible for delivering the electrons to Hdr. Under MIET conditions, H 2 diffuses inside the cell and can be oxidized to the sake of Mph reduction. n-Fe 3 O 4 was found to mimic the Mph role, and therefore a reduction for n-Fe 3 O 4 can occur on the surface of the cell (Figure ). This mechanism was suggested by Fu et al, who used n-Fe 3 O 4 for accelerating the acetotrophic methanogenesis by M. barkeri and noticed the presence of hematite on the surface of M. barkeri .…”
Section: Interspecies Electron Transferring (Iet) Via a Biotic–biotic...mentioning
confidence: 98%
“…Many previous studies highlighted that the electron transfer from NMDs to the electrogenic microbes (e.g., Geobacter sp., Shewanella sp., Desulfovibrio sp., and Syntrophobacter sp.) can be demonstrated by an observed remarkable change in the expression of genes encoding certain enzymes, and cofactors, e.g., F 420 , ,, Pil A, and omcS . , F 420 cofactor is generated from the oxidation of F 420 H 2 , coupled with methanophenazine reduction, by membrane-bound Fpo complex. ,, The fundamental role of the F 420 cofactor is to transport electrons required for the reduction of CO 2 (Figure ). The electron donation by F 420 is expected to increase the interaction of NMDs with microorganisms. , Zhuang et al showed that increased conversion of acetate to CH 4 correlated with the concentration of the cofactor F 420 when Fe 3 O 4 was loaded on the water hyacinth-derived biochars.…”
Section: Extracellular Electron Transfer Via a Biotic–abiotic Relatio...mentioning
confidence: 99%
See 1 more Smart Citation